1987
DOI: 10.3382/ps.0660439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brooding Paper on the Performance of Bobwhite Quail

Abstract: Three experiments were conducted to determine the response of bobwhite quail chicks when reared in pens with and without brooding paper. Half the chicks in each experiment was brooded Days 1 to 7 on brooding paper, which covered the litter within a brooder ring. The other half was brooded on either new or reused litter without paper. Results of all three experiments showed a consistent trend of higher 1-week body weights and lower cumulative 1 to 3 week mortality when birds were reared in pens without paper. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Significant differences in feed consumption and feed conversion due to brooding paper were not found in the analysis of Weeks 1 to 3 cumulative data. These results suggest less feed wastage by Bobwhite quail chicks brooded on brooding paper during the 1st wk and are in agreement with results of Ouart et al (1987). Upon analysis of all experiments, no overall net performance advantages were found for either brooder type, regardless of brooding paper use.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Significant differences in feed consumption and feed conversion due to brooding paper were not found in the analysis of Weeks 1 to 3 cumulative data. These results suggest less feed wastage by Bobwhite quail chicks brooded on brooding paper during the 1st wk and are in agreement with results of Ouart et al (1987). Upon analysis of all experiments, no overall net performance advantages were found for either brooder type, regardless of brooding paper use.…”
Section: Resultssupporting
confidence: 91%
“…Brooding paper was used in these experiments because previous results suggested that there might be a brooder attractant light source by brooding paper interaction on performance. Ouart et al (1987Ouart et al ( , 1990 reported that both brooding paper and brooder attractant light source affect Bobwhite quail performance. Brooding paper was taken up after 7 days when the brooder ring was removed.…”
Section: Experiments 2 3 Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Analysis of surviving chick weights revealed a significant time (day) by treatment effect (F 1, 10 5 8.25, P , 0.01), and surviving chicks in the experimental group were consistently smaller than those in the treatment group (F 1, 40 5 6.83, P 5 0.01, Table 2). Weight gain of the control group was similar to that measured by Ouart et al (1987).…”
Section: Resultssupporting
confidence: 61%